Democratic Revisability and the Legitimacy of Constitutional Entrenchments: A Content-Specific Approach - Jakob Hohnerlein (German Law Journal)
As modern constitutions bind democratic legislation to entrenched norms, they are in tension with the democratic idea that laws should be open to revision by new majorities. Against a widespread view, constitutional norms cannot be considered to be “more democratic” than ordinary laws due to specific qualities of the constitution-making process. Rather, the higher-level law of constitutions can fulfil a specific function as it may provide standards that ensure that laws made by the majority can be justified to everyone. On that basis, I evaluate for different types of constitutional norms whether there are good reasons for constraining legislation. In particular, entrenching cultural traditions and economic policy is more problematic than guarantees of the democratic process and rights ensuring respect for individuals. In sum, a two-tiered law-making system has important values, but people engaging in constitution-making and constitutional interpretation should be wary that the constitutional form is not abused.